Cloning and localization of two multigene receptor families in goldfish olfactory epithelium - Cao, Yanxiang (National Academy of Sciences, 1998)
Goldfish reproduction is coordinated by pheromones that are released by ovulating females and detected by males. Two highly potent pheromones, a dihydroxyprogesterone and a prostaglandin, previously have been identified, and their effects on goldfish behavior have been studied in depth. We have cloned goldfish olfactory epithelium cDNAs belonging to two multigene G-protein coupled receptor families as a step toward elucidating the molecular basis of pheromone recognition. One gene family (GFA) consists of homologs of putative odorant receptors (≈320 residues) found in the olfactory epithelium of other fish and mammals. The other family (GFB) consists of homologs of putative pheromone receptors found in the vomeronasal organ (VNO) of mammals and also in the nose of pufferfish. GFB receptors (≈840 residues) are akin to the V2R family of VNO receptors, which possess a large extracellular N-terminal domain and are homologs of calcium-sensing and metabotropic glutamate receptors. In situ hybridization showed that the two families of goldfish receptors are differentially expressed in the olfactory epithelium. GFB mRNA is abundant in rather compact cells whose nuclei are near the apical surface. In contrast, GFA mRNA is found in elongated cells whose nuclei are positioned deeper in the epithelium. Our findings support the hypothesis that the separate olfactory organ and VNO of terrestrial vertebrates arose in evolution by the segregation of distinct classes of neurons that were differentially positioned in the olfactory epithelium of a precursor aquatic vertebrate.